POLA AKTIVITAS MASYARAKAT SEBAGAI HIRARKI KAMPUNG NAGA SEBAGAI WARISAN BUDAYA CERDAS - Budiarto, Asri; Sunarmi, Sunarmi; Soewarlan, Santosa (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
The pattern of community activities in Tasikmalaya, Kampung Naga can be identified as a cultural transformation that exists in the neighborhood of the traditional house and can be seen with the expanse of agricultural lands and water ponds at the forefront of the residential area. Overlaying the houses of indigenous people and other facilities in a certain pattern unity. It can be stated that the livelihoods of the indigenous people of Kampung Naga form a village pattern from the available activity lands. The existence of the flow of life of the indigenous people of Kampung Naga as a place to live not only contains the meaning of the village, but the existence of the Ciwulan river as a sign and meaning of life. The customary leader's residence is characterized by the location of the customary leader's house which is in a higher area and becomes the orientation (direction) for the surrounding houses. This research wants to know the flow of the activities of the Kampung Naga community towards the existence of their customs that reflect a strong understanding of the importance of cultural sustainability and tradition. The community realizes that customary activities as a cultural heritage are the basis for their survival, which can be shown by their high involvement and responsibility for their ancestral heritage. The activities of the indigenous people of Kampung Naga as the place where one returns from.As far as someone who leaves one day will return to the place where he was born. So there is a very strong emotional bond between the village and one's soul. The Village Hierarchy in the site in Kampung Naga has characteristics with tiered ascending contours as a local land condition that reflects the adaptation of indigenous activities to the natural environment and local wisdom. This is the same as the identical pattern of Sundanese villages that have distinctive elements also found in the settlement pattern of Kampung Naga. Through settlement patterns as seen in Kampung Naga, the community has historically developed settlement strategies that are in accordance with the activities and characteristics of the environment and social needs.Keywords: Kampung Naga hierarchy, cultural heritageAbstrakPola aktivitas masyarakat di kampung naga Tasikmalaya dapat diidentifikasi sebagai transformasi budaya yang ada dalam lingkungan perkampungan rumah adat dan dapat dilihat dengan adanya hamparan lahan-lahan pertanian dan kolam-kolam air di bagian terdepan pada kawasan permukiman. Hamparan rumah-rumah masyarakat adat dan fasilitas lain dalam kesatuan pola tertentu. Hal ini dapat dinyatakan bahwa mata pencaharian masyarakat adat kampung Naga membentuk pola kampung dari lahan-lahan aktivitas yang tersedia. Adanya aliran kehidupan masyarakat adat Kampung Naga sebagai tempat tinggal yang tidak hanya mengandung arti kampung, tetapi adanya sungai Ciwulan sebagai tanda dan makna kehidupan. Tempat tinggal pimpinan adat ditandai oleh Letak rumah ketua adat yang berada di daerah lebih tinggi dan menjadi orientasi (arah) bagi rumah warga yang ada disekitarnya. Penelitian ini bertujuan untuk mengetahui alur aktivitas masyarakat Kampung Naga terhadap eksistensi adat istiadat mereka yang mencerminkan pemahaman kuat akan pentingnya keberlanjutan budaya dan tradisi. Masyarakat menyadari bahwa aktivitas adat sebagai warisan budaya merupakan dasar bagi kelangsungan hidupnya dapat di tunjukkan dengan keterlibatan dan tanggung jawab yang tinggi terhadap warisan leluhur mereka. Aktivitas masyarakat adat Kampung Naga sebagai tempat asal seseorang kembali (bali geusan ngajadi). Sejauh-jauhnya seseorang yang pergi suatu saat akan kembali lagi ketempat asalnya dilahirkan. Sehingga ada ikatan emosional sangat kuat antara kampung dengan jiwa seseorang. Hirarki Kampung dalam tapak di Kampung Naga memiliki karakteristik dengan kontur naik berjenjang sebagai keadaan tanah setempat yang mencerminkan adaptasi aktivitas masyarakat adat terhadap lingkungan alam dan kearifan lokal. Hal ini sama sebagai identik pola perkampungan masyarakat Sunda yang memiliki elemen khas juga ditemukan di dalam pola pemukiman Kampung Naga. Melalui pola pemukiman seperti yang terlihat di Kampung Naga, masyarakatnya secara historis telah mengembangkan strategi pemukiman yang sesuai dengan aktivitas dan karakteristik lingkungan dan kebutuhan sosialnya.Kata Kunci: Hirarki Kampung Naga, Warisan budaya Authors:Asri Budiarto : Institut Seni Indonesia SurakartaSunarmi : Institut Seni Indonesia SurakartaSantosa Soewarlan : Institut Seni Indonesia SurakartaReferences:Adimihardja, K. (1993). Kebudayaan dan Lingkungan. Bandung: Ilham Jaya.Anto, A. A., Sunarmi, & Soewarlan, S. (2024). Kampung Naga¯: Exploration of Traditional Architecture and. Lakar: Jurnal Arsitektur, 07(01), 85“100. https://doi.org/http://dx.doi.org/10.30998/lja.v7i1.22100Basrowi. (2005). Pengantar Sosiologi. Bogor: Ghalia Indonesia.Koentjaningrat. (2009). Pengantar Ilmu Antropologi. Jakarta: PT Rineka Cipta.Linton, R. (1984). Antropologi, Sutau Penyelidikan tentang Manusia. Bandung: Jemmars.Maslucha, L. (2009). KAMPUNG NAGA: Sebuah Representasi Arsitektur sebagai Bagian dari Budaya. El-HARAKAH, 11(1), 35“49. https://doi.org/10.18860/el.v1i1.421Mikaresti, P., & Mansyur, H. (2022). Pewarisan Budaya Melalui Tari Kreasi Nusantara. Gorga¯: Jurnal Seni Rupa, 11(1), 147-155. https://doi.org/10.24114/gr.v11i1.33333Oktovan, R. N., Suryamah, D., & Dwiatmini, S. (2020). Pewarisan Budaya dalam Kesenian. Jurnal Budaya Etnika, 4(2), 114“125. https://jurnal.isbi.ac.id/index.php/etnika/article/view/1566Padma, A. (2001). Kampung Naga, Permukiman Warisan Karuhun. Bandung: Foris.Ranjabar, J. (2006). Sistem Sosial Budaya Indonesia: Suatu Pengantar. Bogor: PT Ghalia Indonesia.Rusnandar, N. (2013). Seba¯: the Culmination of Baduy ™S Religious Ritual in Kabupaten (Regency) Lebak, The Province Banten. Patanjala, 5(1), 83“100. https://doi.org/http://dx.doi.org/10.30959/patanjala.v5i1.163Sonia, T., & Sarwoprasodjo, S. (2020). Peran Lembaga Adat dalam Pelestarian Budaya Masyarakat Adat Kampung Naga, Desa Neglasari, Kecamatan Salawu, Tasikmalaya. Jurnal Sains Komunikasi Dan Pengembangan Masyarakat [JSKPM], 4(1), 113“124. https://doi.org/10.29244/jskpm.4.1.113-124Syukri, A., Azis, A. C. K., Olendo, Y. O., Elpalina, S., & Syam, C. (2023). Koleksi Museum Adityawarman¯: Sebagai Sumber Belajar Seni Dan Budaya. Gorga: Jurnal Seni Rupa, 12(November), 488“494. https://doi.org/https://doi.org/10.24114/gr.v12i2.51471Tri Sulistyo, E., & Sunarmi. (2021). Emotional Intelligence And Balanced Personality In Javanese Cultural. Intelligence And Balanced Personality In Javanese Cultural Understanding-Palarch™s Journal Of Archaeology Of Egypt/Egyptology, 18(4), 3344. https://archives.palarch.nl/index.php/jae/article/view/6827Widjaja, A. W. (1986). Komunikasi dan Hubungan Masyarakat. Jakarta: Bina Aksara.